Social Media Advertising, Fear of Missing Out (FOMO), and Impulsive Purchase Decision of iPhone among Generation Z in Indonesia: Evidence from Jambi City - B., Sylvia Kartika Wulan; Widiastuti, Fitri; Chairunnisa, Fitri; Rosyid, Garry Yuesa (International Journal of Science and Society, 2025)
This research investigates the mediating role of Fear of Missing Out (FOMO) in the relationship between social media advertising and impulsive purchase decisions among Generation Z consumers in Jambi City, Indonesia. Using a quantitative survey and Structural Equation Modeling with Partial Least Squares (SEM–PLS), data from 199 respondents were analyzed. Results indicate that social media advertising exerts a weak direct influence on impulsive buying (β = 0.09, p > 0.05), while FOMO has a strong and significant positive effect (β = 0.62, p < 0.001). Furthermore, social media advertising significantly influences FOMO (β = 0.68, p < 0.001), which mediates its relationship with impulsive purchasing (indirect effect β = 0.42, p < 0.001). The findings demonstrate that emotional and social triggers outweigh direct marketing exposure in shaping impulsive consumption among Gen Z. The study contributes to the theoretical understanding of affective mechanisms in digital marketing and offers managerial insights for responsible and ethical branding.